Design of Banana Slicing Machine - Mohd Afiq Danial Bin Khairull Azhar; Abd Khalil Bin Abd Rahim; Mahmod Abd Hakim Bin Mohamad (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Banana Chips is one of the famous chips in Malaysia especially during Celebration of “Hari Raya”. The demand will be high during this celebration. Slicing process is one of the important process in the making of Banana Chips. The productivity of the banana chips depend on how fast the banana slices can be sliced. Slicing using manual technique required more human energy and take a long time. To overcome this problem, Banana Slicing Machine have been designed to increase the productivity and reduce time consuming in the making of banana chips. This project used George E Dieter design process for design this machine. The design process consists of eight phase which are Define problem, Gather information, Concept generation, Concept evaluation, Product architecture, Configuration design, Parametric design and Detail design. The existing patent and available machine were referred to generate idea for the banana slicing machine. The selected idea and concept then will be modelled using Solidwork Software. Solidwork Software also being used to conduct some engineering analysis and Life Cycle Assessment (LCA). The author also making analysis using theoretical calculation. The result of the analysis shows that the machine can produce 64.8kg slices of banana in one hour. The overall dimension of the banana slicing machine is 700mm x 600mm x 755mm with the weight of 57 kilogram.